Admittance Relaxation Time Distribution (aRTD) for Quantification of Protein Concentration - Wicaksono, Arbariyanto Mahmud; Kawashima, Daisuke; Takei, Masahiro (IEEE sensors journal, 2025)
The admittance relaxation time distribution (aRTD) has been proposed for the quantification of protein (albumin and ɣ-globulin) concentration c . The aRTD extracts peaks of distribution function ɣ [S] at relaxation times τ [s] from measured admittance Y [S]. In order to clarify the relationship between ɣ, τ , and c , aRTD was performed on solutions and porcine subcutaneous adipose tissue (SAT) with an injected current frequency f from 10 Hz to 1 MHz under the albumin concentration ^{\text {Alb}} {c} of 0.80-2.30 g/dL, the ɣ-globulin concentration ^{\text {Glo}} {c}~R ^{{2}} above 0.8, which is much larger than R ^{{2}} between c and P1 extracted by iRTD. The aRTD on SAT provides additional correlation through ɣP2 at τ _{\text {P2}} , which increases proportionally to ^{\text {Glo}} {c} and inversely proportional to ^{\text {Alb}} {c} and ^{\text {PM}} {c} . The average fitting error ε of aRTD is, moreover, smaller than ε of iRTD by 12%, which highlights aRTD accuracy in the fitting.